Analysis of Losses Experienced by Gakoptas in the Dispute Case with PT Torus Ganda: Legal and Economic Perspective: Case Study Analysis of Supreme Court Decision No.2642/K/PID/2006 - Aura Preety Adisty; Muhammad Dzaky Epindo; Anu Berkat Kornelius Gulo; Bambang Fitrianto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The dispute case between Gakoptas and PT Torus Ganda caused problems. PT Torganda illegally controlled Gakoptas land which caused a conflict, as a result a farmer was injured. This study aims to determine the causal factors and resolution strategies in the dispute case between Gakoptas and PT Torganda. This study uses a normative juridical method with the sources of materials used in the form of secondary, primary and tertiary sources. The results of this study state that the causal factors of the conflict are due to the land administration system, inequality in the distribution of land ownership, legality of land ownership and economic motives. The resolution strategy can be carried out by executing the Supreme Court's decision, land redistribution through agrarian reform, land controlled by PT Torganda is returned to Gakoptas, economic recovery and sanctions.